Female Planners in the Workplace and in Planning Practice - Moraka, Sedimogang (UNIVERSITY OF WITWATERSRAND FACULTY OF ENGINEERING & THE BUILT ENVIRONMENT, 2016)
“Freedom cannot be achieved unless WOMEN have been emancipated from all forms of oppression. Our endeavours must be about the liberation of the WOMAN, the emancipating of the man and the liberty of the child” (Extract from a speech at opening of first democratic parliament by former SA President-, Nelson Mandela 1994) The above quote symbolizes the start of a new era, when all forms of oppression upon all men and women of different races are eliminated. Liberty was the driver of the new democratic South Africa and encompassed the drafting of new liberation policies. Its impacts included the entry of women in varied sectors of the work force, especially areas of work which were regarded as male domains. However, liberty is an immeasurable concept as it is relative to the person being liberated. The article written by Olusola Olufemi (2008) on the experiential and emotional encounters of women planners in Sub-Saharan Africa, provides a clear account of women through their entry into the male dominated planning profession; and found that they still facing different kinds of oppression.The types of oppression mentioned in her article are deemed to be tested in the current state of the planning profession and can only be known by the sharing of experiences of female planners in the workplace and planning practice.The research study does not only aim to obtain findings on the current experiences of female planners in the workplace, but also to understand the effect that the workplace context has on the planning pursuits and practices of the female planner. The research report comprises of documented experiences of women in the public, private and parastatal sectors, who occupy varied planning positions, with the second and the third chapters reviewing the foundational academic literature on women and planning as well as women’s incorporation into the planning profession.The research report concludes by elaborating on the findings of the relationship between the experiences of the workplace and its effect on the female planner’s planning practice. It also
How does their workplace contexts affect their presence in the profession and their involvement in gender sensitive planning practices?
Honours Research Report 2016